Uji aktifitas anti nyamuk dari ekstrak etanol daging kulit buah durian (Durio zibethinus Murr) terhadap nyamuk Aedes aegypti dalam sediaan krim - Sagita, Desi; Kristanto, Nur; Dachriyanus, Dachriyanus (Tropharm (Trobosan Pharmacy); Vol 1 No 1 (2015): Tropharm (Trobosan Pharmacy), 2021)
Tests were conducted anti-mosquito activity from rind extracts of durian meat (Durio zibethinus Murr ) against Aedes aegypti in cream. Ethanol 96% used for extraction of durian rind. Evaluation cream preparation includes organoleptic test, homogeneity test, power spread test, pH test, stability test, irritation test and type cream test. Research results showed that the concentrations of the durian fruit peel extract (0%, 5%, 10% and 15%) in the cream preparation affects the length of time the mosquito Aedes aegypti is upon the hands of the panelists and the amount of activity is influenced by the amount of meat extract content of durian rind inside cream preparation.